PEMBELAJARAN MEMBACA AL QUR’AN DENGAN METODE YANBU’A DAN METODE IQRO’ - Khasanah, Muhimatun; Sakir, Moh.; Mubin, Nurul (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2024)
This study aims to describe the learning process of reading the Qur'an at MI Islamiyah Jolontoro and MI Ma'arif Bendosari in Sapuran. The objectives of this research are: (1) to explore the Qur'an reading instruction using the Yanbu'a method at MI Islamiyah Jolontoro; (2) to describe the Qur'an reading instruction using the Iqro' method at MI Ma'arif Bendosari; and (3) to analyze and compare the implementation of the Yanbu'a and Iqro' methods at both institutions. This research employed a qualitative approach with a multi-case study design, conducted at MI Islamiyah Jolontoro and MI Ma'arif Bendosari. Data were collected through observation, interviews, and documentation. The data analysis involved several stages, including data collection, data reduction, drawing conclusions, and cross-site analysis. The validity of the data was ensured through technical triangulation and source triangulation. The findings reveal that: (1) At MI Islamiyah Jolontoro, the Yanbu'a method is implemented through a structured process consisting of planning, implementation, and evaluation. Special attention is given to lower-grade students who have not yet mastered Qur'anic reading. The use of visual aids significantly enhances students’ comprehension. (2) At MI Ma'arif Bendosari, the Qur'anic reading is conducted using the Iqro' method, which also follows the stages of planning, implementation, and evaluation. The teachers are classroom teachers rather than external Qur'an instructors. This learning takes place at the end of the school day, where students take turns reading aloud and are assessed directly by their teacher. (3) The most significant differences between the two institutions include the choice of method, the timing of the instruction, the selection of instructors, and the use of visual aids. MI Islamiyah also incorporates tawasul (a form of spiritual dedication) to the book’s author. Despite these differences, both methods apply the CBSA approach (Cara Belajar Siswa Aktif or Active Student Learning), which emphasizes physical, mental, intellectual, and emotional engagement in learning. Both institutions also employ the sorogan technique during implementation and use Qur’an control books for assessment.